Spike & Dru : pretty maids all in a row - Golden, Christopher (New York : Pocket Books, 2001)
Spike, determined to present his monster lover Drusilla with the legendary magical necklace Freya's Strand for her birthday, agrees to infiltrate the Watchers' Council and kill the current Slayer, as well as all the Slayers in training, if the demon Skrymir will turn over the jewels.
"An original novel based on the hit TV series created by Joss Whedon.".
Booklist.
Books for the Teen Age (NYPL).
Publisher's Weekly.
Adult.
Adult
Keywords: Buffy the Vampire Slayer (Fictitious character) -- Fiction; Vampires -- Fiction; Buffy the Vampire Slayer (Fictional character) -- Fiction; Vampires -- Fiction